Luminescence properties of chlorine molecules in glassy SiO2 and optical fibre waveguides - Skuja, Linards; Kajihara, Koichi; Smits, Krisjanis; Alps, Kalvis; Silins, Andrejs; Teteris, Janis (Estonian Academy Publishers, 2017)
Glassy SiO2 is the basic material for optical fibre waveguides and manufacturing-induced Cl impurities reduce their transparency in UV spectral range. This work reports in-depth study/spectroscopic parameters of the near-infrared (1.23 eV) low-temperature photo-luminescence (PL) of interstitial Cl2 molecules in SiO2. The zero-phonon line position was estimated at 2.075 eV on the basis of anharmonicity of Cl2 PL vibronic data. The vibronic sub-bands are broadened by coupling to phonons and by an additional contribution from the glassy disorder. The Huang‒Rhys factor is ≈13. The PL decay time is between 1 and 10 ms in the temperature range 100 K‒13 K and can be reproduced by 3 exponents. Cl2 PL retains relatively high quantum yield and its characteristic structured shape, when the temperature is increased from 13 K to the liquid nitrogen temperature. This allows using it conveniently as a high-sensitivity diagnostic tool for detecting Cl2 impurities in optical fibre waveguides. Time-resolved measurements of optical fibre waveguides indicate that the lower detection limit is below 1010 Cl2/cm3.
The support from Latvian Research Program IMIS 2, project “Photonics and materials for photonics” is acknowledged. K.K. was partially supported by the Collaborative Research Project of Materials and Structures Laboratory, Tokyo Institute of Technology. The publication costs of this article were covered by the Estonian Academy of Sciences and the University of Tartu.
Keywords: photonics; amorphous SiO2; luminescence; Cl2 impurities; optical fibres; Research Subject Categories::NATURAL SCIENCES:Physics